Poor sleep quality and its predictors among type 2 diabetes mellitus patients attending Jimma University Medical Center, Jimma, Ethiopia - Tadeg Jemere; Andualem Mossie; Hiwot Berhanu; Yigizie Yeshaw (BMC Research Notes, 2019)
Abstract Objectives The aim of this study is to determine the prevalence of poor sleep quality and its associated factors among people with type 2 diabetes mellitus at Jimma University Medical Center, Jimma, Ethiopia 2018. Comparative cross-sectional study was employed on 198 participants (99 cases and 99 controls). Data were collected using Pittsburgh Sleep Quality Index (PSQI) and analyzed using SPSS version 20. Variables with p value ≤ 0.05 in multivariable logistic regression were treated as significant predictors of poor sleep quality. Results The prevalence of poor sleep quality was 55.6% among people with type 2 diabetes mellitus and 32.3% among controls. Longer duration of diabetes since diagnosis (> 10 years) [AOR = 4.88 CI (1.27, 18.66) p = 0.021], co-morbid hypertension [AOR = 3.2, CI (1.16, 8.84) p = 0.025], poor glycemic control [AOR = 3.16 CI (1.2, 8.27), p = 0.02] and current khat chewing [AOR = 3.06, CI (1.04, 8.98), p = 0.042] were factors significantly associated with poor sleep quality. The prevalence of poor sleep quality was significantly higher among people with diabetes than those who didn’t have diabetes (controls). Poor sleep quality may bring about mental impairment and reduce working capacity of individuals with diabetes mellitus. Therefore, diabetes mellitus patients need to have heath education about risk factors for poor sleep quality.